Pengaruh Participatory Leadership, Supportive Culture Organization pada Job Satisfaction Dimediasi oleh Work-Life Balance - Yoga Ebeth Cahya Maryanto; Widya Prananta (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to analyze the influence of participatory leadership, supportive organizational culture, and work-life balance on employee job satisfaction. The research method employs a quantitative approach, using SEM-PLS analysis of data collected from PKWT employees at PT Graha Satu Tiga Tujuh. The results show that participatory leadership and supportive organizational culture have a positive and significant effect on job satisfaction, while work-life balance has no proven effect. Furthermore, work-life balance does not mediate the relationship between leadership and organizational culture with job satisfaction. These findings confirm that internal organizational factors, particularly leadership quality and work culture, have a greater impact on employee satisfaction than work-life balance. This study provides practical contributions to human resource management by offering strategies to enhance job satisfaction by strengthening leadership and organizational culture.